Dimensions of the impact of urinary incontinence on quality of life of affected women: a review of the English literature. Issue 2 (4th April 2014) - Seshan, Vidya; Muliira, Joshua Kanaabi
ABSTRACT Urinary incontinence (UI) is a condition encountered by many women in their middle ages and although it is not life threatening, it tremendously affects the quality of life (QOL) of affected women. The purpose of this review was to characterize the dimensions of women's QOL affected by UI. A systematic review of published literature reporting about primary studies was conducted using specific Medical Subject Headings (MeSH) terms: (urinary incontinence) and 1 – (quality of life), 2 – (outcome), 3 – (well‐being), 4 – (health outcomes), 5 – (women), 6 – (social well fair) and 7 – (signs and symptoms). This yielded 545 articles and 12 articles met the inclusion criteria. Searches were conducted from electronic databases including PubMed, CINHAL and SCOPUS. The studies included in the review used different measurements to reach conclusion about the effect of UI on QOL. All the studies emphasized that UI has a negative impact on at least two aspects of the affected woman's QOL. The results of the review show that UI negatively impacts women's QOL in four main dimensions such as physical health, mental health, sexual health and social well‐being. UI negatively impacts affected women's in various aspects of their life and to effectively address their health care needs it requires a multidisciplinary and holistic approach to their health care needs.